A New Model for Prediction of Heat Eddy Diffusivity in Pipe Expansion Turbulent Flows (Iranian Journal of Chemical Engineering)
A new model to calculate heat eddy diffusivity in separating and reattaching flows based on modification of constant Prt is proposed. This modification is made using an empirical correlation between maximum Nusselt number and entrance Reynolds number. The model includes both the simplicity of Prt=0.9 assumption and the accuracy of two-equation heat-transfer models. Furthermore, an appropriate low Reynolds number k — e model is adopted for calculation of eddy viscosity. The model is used for prediction of Nusselt number distribution at various ranges of Reynolds number and expansion ratio. The numerical results are compared with available experimental data in the literature and have shown good agreement. The CPU time for the present model is about 33% less than that of two-equation heat-transfer model.